STUDY OF MICRO HYDRO ELEKTRICAL POWER PLANT at WAY NGISON RIVER TRIHARJO KEBAGUSAN VILAGE GEDONG TATAAN SECTOR DISTRICT OF PESAWARAN - Bagus W, Subekti; Sugiri, Agus; Risano, A.Yudi Eka (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
Electricity become one of the basic needs of industrial and human life. It is shown by the electrical peripherals and industrial machineries which consumes a lot of energy. By the increasing of human population and the electricity consumtion turbine is the most common that used to produce electricity using the renewable energy resources such as hydro, wind, sea wave which it can solve the problem of increasing electricity consumtion. renewable energy sources. This source is readily used from many creeks and rivers that has a high enough flow and water debt which easily found surround us. The purpose of this with title “Feasibility Study Micro Hydroelectric Power Station (PLTMH) Using Cross fllow Turbine at Triharjo desa Kebagusan Kecamatan Pesawaran Bandar Lampung” is to contributed in hydro turbine management and to planning a micro hydroelectric power station that can be used and applied for a better life. Based on the field data, (Head = 12 m and water debit = 0,0584m3/s) the Cross Fllow Turbine can produce energy 5,10 kW. Bellow to the data above it is result that the Way ngison Dusun triharjo Desa Kebagusan dam can be set a micro hydro electric power.Keywords : micro hydroelectric power station, water dept, crossflow Turbine.